A SYNTHETIC FLUID INCLUSION STUDY OF COPPER SOLUBILITY IN HYDROTHERMAL BRINES FROM 525 TO 725 °C AND 0.3 TO 1.7 GPA - Hack A.C.; Mavrogenes J.A. (My University, 2006)
Fluid inclusions were synthesized in a piston-cylinder apparatus under mineral-buffered conditions over a range of Cl concentration (0.29 to 11.3 mol kg-1), temperature (525 to 725 °C), and pressure (0.3 to 1.7 GPa). All fluids were buffered by the mineral assemblage native copper + cuprite + talc + quartz. In situ fluid composition was determined by analysing individual fluid inclusions by LA-ICPMS and independently analysing the quench solution. The solubility data provide basic information necessary to model the high temperature behaviour of Cu in magmatic-hydrothermal systems. Copper concentrations up to ~15 wt% were measured at 630 °C and 0.34 GPa. These results give an upper limit for Cu in natural fluids and support field-based observations of similar high Cu concentrations in fluids at near-magmatic conditions. Experimental evidence indicates that Cu+ may form neutral chloride complexes with the general stoichiometry CuCl (HCl)n - 10 with n up to 4, though n ≤ 2 is typical for the majority of the experimental conditions. At high pressure (>~0.5 GPa) there is evidence that hydroxide species, e.g., CuOH0, become increasingly important and may predominate over copper(I)-chloride complexes. The roles of fluid mixing, cooling and decompression in ore-forming environments are also discussed. © 2006 Elsevier Inc. All rights reserved.